Human Primary Cell-Based Organotypic Microtissues for Modeling Small Intestinal Drug Absorption - Ayehunie, Seyoum; Landry, Tim; Stevens, Zachary; Armento, Alex; Hayden, Patrick; Klausner, Mitchell (Pharmaceutical research, 2018)
Purpose The study evaluates the use of new in vitro primary human cell-based organotypic small intestinal (SMI) microtissues for predicting intestinal drug absorption and drug-drug interaction. Methods The SMI microtissues were reconstructed using human intestinal fibroblasts and enterocytes cultured on a permeable support. To evaluate the suitability of the intestinal microtissues to model drug absorption, the permeability coefficients across the microtissues were determined for a panel of 11 benchmark drugs with known human absorption and Caco-2 permeability data. Drug-drug interactions were examined using efflux transporter substrates and inhibitors. Results The 3D–intestinal microtissues recapitulate the structural features and physiological barrier properties of the human small intestine. The microtissues also expressed drug transporters and metabolizing enzymes found on the intestinal wall. Functionally, the SMI microtissues were able to discriminate between low and high permeability drugs and correlated better with human absorption data (r 2 = 0.91) compared to Caco-2 cells (r 2 = 0.71). Finally, the functionality of efflux transporters was confirmed using efflux substrates and inhibitors which resulted in efflux ratios of >2.0 fold and by a decrease in efflux ratios following the addition of inhibitors. Conclusion The SMI microtissues appear to be a useful pre-clinical tool for predicting drug bioavailability of orally administered drugs.